Commemoration of the 25th anniversary of Dr. Samuel Goldstern leading the Fango Clinic in Vienna. In centre Samuel and Maria, Helene is behind Maria (1929)
Commemoration of the 25th anniversary of Dr. Samuel Goldstern leading the Fango Clinic in Vienna. In centre Samuel and Maria, Helene is behind Maria.